KONFLIK SUNNI-SYIAH DI INDONESIA - Resta Tri Widyadara (UIN Sunan Kalijaga Yogyakarta, 2015)
This article discusses confl icts between the Sunnite and the Shi’ite in Indonesia. It wasbegan by discussing the Shia emergence history, development of the Middle East Shiaand development and inclusion of the Shi’ite in Indonesia. The Shi’ite identity cannotbe seen easily in Indonesia context. The Shi’ite spread in the community and did notlive in groups in a particular region. The Shi’ite that came to Indonesia was like thespread of Islam in accordance with the understanding spreader. The infl ux of Shia inIndonesia is still being debated in academic circles. Hasjmi stated that the Shia encounterinto Indonesia was brought by Muslim Persian traders, Arabic, Gujarat and India. TheShi’ite established the Islamic Empire in Perlak. In different perspective, AzyumardiAzra argued that there was no suffi cient evidence of the spread of the Shiite in the earlydays of Islam in the archipelago and also asserted that Shia was popular in Indonesiahas not been so long, especially after the Iranian revolution in 1979. The Shiites havelong coexisted with a Sunni group that became the majority in Indonesia. In addition,the Shia has come into the existing reality in the midst of the Indonesian nation. Theinfl uence of the Shia’s teachings and its thought of schools grew rapidly in Indonesia. It ischaracterized by the number of study groups that focus on the study of Shia. Shia becamea part of Indonesian national diversity that has not received strong protection of law,as well as considered outside of Sunni ideologies. In fact, Shia became a minority groupin Indonesia. The lack harmonious relationship between the Shi’ite and the Sunnite inIndonesia was motivated by the difference of understanding toward religious teaching andthe lack of tolerance, so there is less of a dispute and even confl ict.